The Modernization Project and its Resistances: the Case of Tobacco - Rodríguez Díaz, Susana (Nómadas. Critical Journal of Social and Juridical Science, 2011)
In this article we will focus on the resistance against the institutional actions in relation to tobacco, which are part of a modernization project that tries to lead society towards its perfection, and are oriented to produce a radical change in the social valoration and activity in relation to the habit of smoking. Ideologies and practices implicit in the modern ways of social control have not been completely assimilated, as the case study of the tobacco shows. Tobacco, nonetheless, keeps a lot of the positive values that, among the centuries, have made it so popular.